Capitalization of capital gains taxes: (In)attention and turn-of-the-year returns - Sebastian Eichfelder; Mona Lau (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
We argue that the tax capitalization effect is a function of the attention of market participants. Market reactions can therefore be driven not only by the announcement dates of tax events but also by factors influencing the dissemination of tax information, such as deadlines and media reports. Analyzing the introduction date of the earlier-announced German capital gains tax reform of 2009 by triple-difference estimation, we find evidence of a delayed market reaction long after the announcement date. Within the last two (five) trading days before the deadline, we observe a sharp increase in abnormal trading volumes of 151.7% (104.0%). The aggregate abnormal return of the German capital market in the last five trading days in 2008 was 10.6%. Furthermore, we find a significant and positive correlation between trading volumes and measures for awareness of the upcoming tax reform (Google searches and media reports).
Keywords: G02; G12; H24; M41; 330; capital gains tax; asset pricing; tax awareness; tax arbitrageM; turn-of-the-year effect; market efficiency